Double-actuator position-feedback mechanism for adjustable sensitivity in electrostatic-capacitive MEMS force sensors - Nastro, Alessandro; Ferrari, Marco; Ferrari, Vittorio (Sensors and actuators. A. Physical., 2020)
[Display omitted] •Novel double-actuator position-feedback mechanism for MEMS force sensors.•Adjustable force sensitivity and measurement range independently from the desired working position.•Servo-assisted position-feedback loop ideally offers infinite input mechanical impedance.•The mechanism has been experimentally validated on a MEMS device employing the gravity force.•Sensitivity from 2.34 to 8.43 V/μN with measurement range from [-217, 226] down to [-20.5, 21.4] nN. This paper presents a novel double-actuator position-feedback mechanism for micro electro-mechanical electrostatic-capacitive force sensors. Compared to a single-actuator position-feedback operation, the innovative use of two independent electrostatic actuators allows to obtain electrically adjustable force sensitivity and measurement range independently from the working position and the stiffness of the internal mechanical movable structure of the device. Additionally, the proposed configuration allows to electrically set and keep fixed the working position of the force probe tip thanks to the position-feedback loop, thus ideally offering an infinite input mechanical impedance, irrespectively from the force measurement range and sensitivity adjusted to the desired values. The proposed mechanism has been experimentally validated on an electrostatic-capacitive MEMS device that includes a capacitive position sensor and a pair of electrostatic actuators, employing the gravity force to provide accurate and repeatable values for the external applied force. The obtained experimental results are in good agreement with both theoretical predictions and parametric numerical analyses. The proposed mechanism allows to adjust the sensitivity in the range from 2.34 up to 8.43 V/μN with a corresponding force measurement range, defined at a maximum nonlinearity error of 1% referred to the full scale, from [-217, 226] down to [-20.5, 21.4] nN, respectively. The measurement repeatability, which sets the resolution of the MEMS force sensor, has been estimated at one standard deviation σ resulting in 345 pN.